2022
DOI: 10.3390/microorganisms10020323
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biochemical Parameters, Rumen Fermentation, and Rumen Bacterial Communities Are Partly Driven by the Breed and Sex of Cattle When Fed High-Grain Diet

Abstract: Hybridization in bovines is practiced with the main aim of improving production performance, which may imply the microbial variations in the rumen from the parental breed cross to their progeny. Besides, the interactions of offspring breed with sex in terms of rumen bacteria are not clear. This study aims to evaluate the variations in rumen bacterial communities in different breeds and sexes, and the correlations among fattening performance, serum biochemical parameters, and rumen fermentation. Forty-two 19.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…In this study, Prevotellaceae and Rikenellaceae (Bacteroidetes), Fibrobacteraceae (Fibrobacteres), Lactobacillaceae (Firmicutes), WCHB1_41 (Verrucomicrobia), and Kiritimatiellaeota were significantly enriched in the feces of Thoroughbred horses. Prevotellaceae has enzymes and gene clusters capable of fermenting and utilizing complex polysaccharides, and the abundance of the bacterial family in the gut is influenced by breed and gender ( 31 ). The RC9 gut group of Rikenellaceae increased the apparent digestibility of acid detergent fiber and neutral detergent fiber, thus improving the dry matter intake of animals ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Prevotellaceae and Rikenellaceae (Bacteroidetes), Fibrobacteraceae (Fibrobacteres), Lactobacillaceae (Firmicutes), WCHB1_41 (Verrucomicrobia), and Kiritimatiellaeota were significantly enriched in the feces of Thoroughbred horses. Prevotellaceae has enzymes and gene clusters capable of fermenting and utilizing complex polysaccharides, and the abundance of the bacterial family in the gut is influenced by breed and gender ( 31 ). The RC9 gut group of Rikenellaceae increased the apparent digestibility of acid detergent fiber and neutral detergent fiber, thus improving the dry matter intake of animals ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Rikenellaceae_RC9_gut_group belongs to the family Rikenellaceae , which plays a role in the fermentation of carbohydrates or proteins (Su et al, 2014 ; Yan et al, 2018 ). Qiu et al ( 2022 ) found that its relative abundance was positively correlated with rumen pH, dietary fiber, and acetate to propionate ratio. However, the greater relative abundance of Rikenellaceae_RC9_gut_group was observed at high media pH in the present study and the inconsistent results may be attributed to the different animal species (dairy vs. beef cattle).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the greater relative abundance of CAG-352 at high media pH was noticed, but the role of CAG-352 during rumen fermentation is still limited. A recent study demonstrated a negative correlation between the relative abundance of CAG-352 with serum concentration of glucose and a positive correlation with serum concentrations of creatinine, total protein, albumin, alkaline phosphatase, and non-esterified fatty acid in cattle (Qiu et al, 2022 ). In addition, the changes in relative abundances of several species at phylum and genus levels with supplementation of C. butyricum at both media pH levels in the current study may be contributed by the nutritional factors (enzymes and vitamins) produced by C. butyricum .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that supplementation with methionine does not affect the production of volatile fatty acids by microorganisms ( Table 6 ). This suggested that methionine supplementation under the present experimental conditions had little effect on the fermentative capacity of the rumen microorganisms, but the ratio of acetic acid to propionic acid changed, and we speculated that the fermentation pattern in the rumen may have changed [ 66 ]. PCoA analysis and adonis analysis based on unweighted UniFrac distance, Bray–Curtis distance, and weighted UniFrac distance matrices showed significant differences in the Bacteroidota structure among the three groups of sika deer ( Figure 3 , Table 7 ).…”
Section: Discussionmentioning
confidence: 99%